The social contingency of momentary subjective well-being - Rutledge, Robb B. (Nat Commun, 2016)
Although social comparison is a known determinant of overall life satisfaction, it is not clear how it affects moment-to-moment variation in subjective emotional state. Using a novel social decision task combined with computational modelling, we show that a participant's subjective emotional state reflects not only the impact of rewards they themselves receive, but also the rewards received by a social partner. Unequal outcomes, whether advantageous or disadvantageous, reduce average momentary happiness. Furthermore, the relative impacts of advantageous and disadvantageous inequality on momentary happiness at the individual level predict a subject's generosity in a separate dictator game. These findings demonstrate a powerful social influence upon subjective emotional state, where emotional reactivity to inequality is strongly predictive of altruism in an independent task domain.